COMPARISON OF STANDARD NEGATIVE PRESSURE WOUND THERAPY ALONG WITH NEGATIVE PRESSURE WOUND THERAPY PLUS INSTILLATION OF NORMAL SALINE IN ACUTE TRAUMATIC WOUNDS - Maqbool, Asad; Aslam, Muhammad Rizwan; Ahmed, Rao Saood; Mumtaz, Humza; Ali, Syed Iftikhar; Zubair, Usama Bin (Pakistan Armed Forces Medical Journal, 2019)
Objective:To compare the efficacy of standard negative pressure wound therapy with combination of negative pressure wound therapy (NPWT) and instillation of normal saline (NS) in acute traumatic wounds.Study Design: Randomized controlled trial.Place and Duration of Study: CMH Rawalpindi from July to September 2017. Material and Methods:Forty patients of both genders with acute traumatic wounds were included in the study after adequate debridement under appropriate anesthesia. They were divided into two groups by lottery method. In first group i.e. group A, standard negative pressure wound therapy was applied whereas in group B negative pressure wound therapy with instillation of NS was used. Mean number of days required for wound to be ready for the final surgical procedure was calculated for both the groups.Results:Mean age of the patients who participated in the study was 37.98 ± 6.275. The mean time required for the final surgical procedure for conventional group A was 27.4 ± 2.2 days and for group B it was 21.92 ± 3.6 days (p-value